Green bonds and the Sustainable Development Index in Asian countries: Panel data evidence - Hidayat, Ariodillah; Manurung, Arum Bona Uli Septian; Lilianna, Lilianna; Rohima, Siti; Pertiwi, Rasyida; Andaiyani, Sri; Shodrokova, Xenaneira (Publishing House of Wroclaw University of Economics and Business, 2024)
This study aimed to determine the relationship between green bonds issuance and the Sustainable Development Index (SDI) using panel data involving several countries in Asia, namely the Philippines, Indonesia, China, Japan, Thailand, Hong Kong, Korea, Malaysia, and Singapore. The study used secondary data sourced from publications and dynamic statistics provided by the Asian Development Bank and the Human Development Report. The authors applied qualitative analysis in the form of movement analysis of trend data patterns as well as quantitative analysis using Fixed Effect Model (FEM) panel data regression. The results show that green bonds are positively and significantly correlated with the SDI. This indicates that when a country is actively issuing green bonds to finance sustainable projects, it contributes to an overall improvement in sustainable development. To address the challenges of sustainable development, the Philippines, Indonesia, and Thailand governments need to formulate appropriate policy measures. Raising environmental awareness and education is an important priority in order to build public understanding of environmental impacts and the need for sustainable development. In addition, the government should strengthen pro-environmental policies and provide fiscal incentives to support sustainable investment, creating a conducive environment for investors. China has to accelerate the transition from fossil energy sources to renewable energy. Moreover, it is necessary to implement policies that promote energy efficiency in key sectors.
Argumenta Oeconomica, 2024, Nr 2 (53), s. 107-119
Keywords: sustainable development indexes; SDI; green bonds; panel data